2007
DOI: 10.1111/j.1550-7408.2007.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Data and Phylogeny of Nosema Infecting Lepidopteran Forest Defoliators in the Genera Choristoneura and Malacosoma

Abstract: ABSTRACT. Nosema isolates from five lepidopteran forest defoliators, Nosema fumiferanae from spruce budworm, Choristoneura fumiferana; a Nosema sp. from jack pine budworm, Choristoneura pinus pinus and western spruce budworm, Choristoneura occidentalis (Nosema sp. CPP and Nosema sp. CO, respectively); Nosema thomsoni from large aspen tortrix, Choristoneura conflictana; and Nosema disstriae, from the forest tent caterpillar, Malacosoma disstria were compared based on their small subunit (SSU) ribosomal RNA (rRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 36 publications
4
34
0
Order By: Relevance
“…Refardt and Mouton (2007) suggested that compaction of the rRNA in microsporidia caused the loss of processing sites, which then facilitated the processability of such a rearranged cluster. Kyei-Poku et al (2008) speculated that the reverse organization of the rRNA gene in the phylum microsporidia, especially in the Nosema was the result of DNA recombination, with breakage and fusion of the fragment in the reverse orientation. Ribosomal rRNA gene units with both gene orders may have coexisted in the genomes of some microsporidian species.…”
Section: Discussionmentioning
confidence: 99%
“…Refardt and Mouton (2007) suggested that compaction of the rRNA in microsporidia caused the loss of processing sites, which then facilitated the processability of such a rearranged cluster. Kyei-Poku et al (2008) speculated that the reverse organization of the rRNA gene in the phylum microsporidia, especially in the Nosema was the result of DNA recombination, with breakage and fusion of the fragment in the reverse orientation. Ribosomal rRNA gene units with both gene orders may have coexisted in the genomes of some microsporidian species.…”
Section: Discussionmentioning
confidence: 99%
“…In another case, three species of the genus Liebermannia, all from orthopteran insects, are similar in ultrastructure but different in nuclear phase, so that the presence of diplokaryotic spores is removed from the revised genus diagnosis (Sokolova et al 2009). Another example is the taxonomy of Nosema/Vairimorpha clade in which assignment to one of these two genera, formally based upon developmental sequence, is not congruent with phylogenetic relationships, substantiating the need for revision of these taxa (Baker et al 1995;Kyei-Poku et al 2008). It can be therefore expected that after a large-scale readjustment of microsporidian taxonomy, life cycle features will not be used in the diagnosis of microsporidian genera, including Crispospora.…”
Section: Differential Diagnosismentioning
confidence: 97%
“…cPP, Nosema sp. co and Nosema disstriae (Huang et al 2004, tsai et al 2005, Wang et al 2006, Ku et al 2007, Kyei-Poku et al 2008.…”
Section: Discussionmentioning
confidence: 99%